2022
DOI: 10.3390/su14031876
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the Initial Challenge of the COVID-19 Pandemic: Analysis of International Responses and Impact in School and Higher Education

Abstract: This paper presents and analyses solutions where open education and open science were utilised to reduce the impact of the COVID-19 pandemic on education. The COVID-19 outbreak and associated lockdowns created huge challenges in school and higher education, demanding sudden responses which aimed to sustain pedagogical quality. Responses have varied from conservative to radically innovative. Universally, the COVID-19 pandemic disrupted and shocked societies worldwide, and education systems were on the front lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 39 publications
(50 reference statements)
2
36
0
3
Order By: Relevance
“…Other studies [44,45,73] also found that students with special needs or disabilities were not adequately supported for effective e-learning. Even in educational contexts where inclusion is imperative and digital inclusion is embraced, the needs of students with additional support needs were difficult to meet remotely [73][74][75]. Like many other researchers [44,[46][47][48]73], we also documented unequal access to digital resources.…”
Section: Challenges In the Transition To Erlsupporting
confidence: 56%
“…Other studies [44,45,73] also found that students with special needs or disabilities were not adequately supported for effective e-learning. Even in educational contexts where inclusion is imperative and digital inclusion is embraced, the needs of students with additional support needs were difficult to meet remotely [73][74][75]. Like many other researchers [44,[46][47][48]73], we also documented unequal access to digital resources.…”
Section: Challenges In the Transition To Erlsupporting
confidence: 56%
“… Stracke et al (2022) proposed a compilation of thirteen life experiences from policy-makers from different countries related to the perceptions and rapid solutions implemented due to the COVID-19 outbreak. Responses ranged from conservative to radical actions to maintain active educational systems according to the resources and capacities of each country and particularly of every university.…”
Section: Related Workmentioning
confidence: 99%
“…A set of user-driven recommendations for making digital games more accessible to players with diverse sensory abilities is revealed. The COVID-19 pandemic defined the role digital technologies can play in education and their relationships with teacher training, the flexibility of pedagogical processes, and the diversification of strategies and resources [30]. The study of [31] underlines that entertainment video games can be an effective educational tool and beneficial in almost all academic disciplines, particularly foreign language and science.…”
Section: Literature Reviewmentioning
confidence: 99%